Studies on antidermatophytic effect of Allamanda cathertica - Ainun Nahar; Syed Ashrafuzzaman; M.N. Islam; M. Shah Alam (Bangladesh Pharmacological Society, 2010)
Antidermatophytic activity of dichloromethane and methanol extracts of whole plant of Allamanda cathertica was evaluated. Two pathogenic dermatophytes Trichophyton rubrum and Microsporum gypseum were used that were collected from dermatophytoses patients. The dichloromethane extract was moderately active at concentration of 50 µg/disc but exhibited highly potent activity at concentration of 200 µg/disc. The methanol extract was not active against the tested fungi. Dichloromethane extract of A. cathertica may have antidermatophyte constituents that could be useful in ringworm diseases.